Animal tool behavior : the use and manufacture of tools by animals - Shumaker, Robert W.; Walkup, Kristina R.; Beck, Benjamin B. (Johns Hopkins University Press, 2011)
In this revised edition of a landmark publication, Robert W. Shumaker and Kristina R. Walkup join Beck to reveal the current state of knowledge regarding animal tool behaviour. Specific examples involving invertebrates, birds, fish, and mammals describe the differing levels of sophistication of tool use exhibited by animals.